1H/19F large coverage homogeneous transmit coil with dedicated multi-element receive coils. - van Uden, M. J. (2011)
RF excitation and reception offers advantages for absolute quantification of metabolites, drugs and cells in vivo. Capecitabine is a drug taken orally for treatment of liver metastasis in colorectal cancer. It is a prodrug that is preferentially converted to active metabolites in tumor tissue and further catabolized in the liver. Since capecitabine and its metabolites contain a fluorine atom it is possible to assess their distribution in healthy liver tissue and in liver metastases by 19F MRS. Monitoring and quantification of cells, applied therapeutically, in vivo is of major importance to estimate treatment efficacy. It has been demonstrated that combined 1H and 19F MRI allows for positive localization of cells and their quantification directly from image data, in a noninvasive way, without using radio-isotopes. Here we present a new coil setup that is capable of creating a homogeneous transmit RF-field for 19F and 1H in combination with dedicated receive coils for lymph nodes and for the liver to enable drug and cellular monitoring.